PERILAKU PEMANFAATAN ATM KONDOM PARA PEKERJA SEKS KOMERSIAL DAN PELANGGANNYA (Studi Kasus pada Lokalisasi Sumber Luh Dusun Padang Bulan Desa Benelan Kidul Kec. Singojuruh Kab. Banyuwangi) - Novia Luthviatin; Sovi Kurniawan (Jurnal Ilmu Kesehatan Masyarakat, 2007)
Since AIDS (Acquired Immune Deficiency Syndrome) epidemic and cause a commotion the last some years world, emerged a discourse which is likely considered to be [by] the way of most precise to overcome the the disease, that is by condom use. To facilitate the society especially high risk group like CSW (Commercial Sexual Worker), customer and pimp in using condom hence government of initiative of attendance of ATM condom. This Research target is to know the correlation between knowledge and attitude of CSW and also customer in localization of Sumber Luh in Padang Bulan of Countryside of Benelan Kidul of Sub district of Singojuruh of Regency Banyuwangi with the exploiting of ATM condom. This research has the character of analytic with the approach of Case Study. Data obtained with the interview use the instrument questionnaire. Interview conducted at 98 respondent consisted of by 57 CSW and 41 customers. The respondent taken away from by population by using simple random sampling method. Data processed and tested by using Correlation Spearman. The Results show that there are significant correlation between knowledge of CSW and customers about ATM condom with the exploiting of ATM condom, but there are not significant correlation between attitude of CSW and customer about ATM condom with the exploiting of ATM condom. Expected by a local government improve the socialization of about existence of ATM condom and also its benefit and socialize the condom use in the effort preventing spreading STD (Sexual Transmitted Disease) especially HIV /AIDS in society specially high risk group (CSW, customer and pimp).   Key words : knowledge, attitude and exploiting of ATM condom